2022
DOI: 10.1007/s10461-022-03667-9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of HIV Among 1 Million Clients in High-Risk Male Populations in Tanzania

Abstract: The World Health Organization identified men as an essential group to target with HIV testing and treatment strategies;: men who have sex with men (MSM) and male clients of female sex workers (CFSW) account for 35% of new HIV infections globally. Using a cross-sectional design from a community-based HIV prevention project in Tanzania (October 2015–September 2018) and multivariable logistic regression, we identified predictors of HIV seropositivity among men. Of 1,041,343 men on their initial visit to the proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Also, economic pressures and poverty increase the risk of infection in women [23]. In line with our findings, Mbita et al showed that men are more at risk of contracting HIV due to drinking alcohol before sex, not being circumcised, having sex with men, and inconsistent condom use [24]. The results of the present study demonstrated that people with a low level of education significantly increase the odds of membership in high-risk and medium-risk classes compared with low-risk classes.…”
Section: Discussionsupporting
confidence: 90%
“…Also, economic pressures and poverty increase the risk of infection in women [23]. In line with our findings, Mbita et al showed that men are more at risk of contracting HIV due to drinking alcohol before sex, not being circumcised, having sex with men, and inconsistent condom use [24]. The results of the present study demonstrated that people with a low level of education significantly increase the odds of membership in high-risk and medium-risk classes compared with low-risk classes.…”
Section: Discussionsupporting
confidence: 90%
“…While registered nurses’ per-hour labor cost are generally higher than paraprofessional community health workers, nurses have been shown to produce overall cost savings through increased efficiency (e.g., effectively handling more cases in less time, addressing complex clinical questions in real-time to support’s patient informed decision-making), higher program retention of patients, and behavioral outcomes that patients self-sustain over longer periods of time ( 30 , 33 , 34 ). Moreover, nurses’ involvement in the STEP + cbNIMART project has the potential to enhance continuity of care following HIVST by serving as a direct conduit to ART for men whose positive self-test results are confirmed, as well as pre-exposure prophylaxis (PrEP) for men whose self-test results are confirmed to be negative but are at high risk for HIV acquisition through factors such as being uncircumcised, having sexually transmitted infection symptoms, and engaging in harmful drinking of alcohol before sex ( 35 ). Future studies that investigate potential diminishing economic returns of nurses can also provide important evidence to inform HIV policy, clinical practice protocols, and community-based linkage to ART or PrEP implementation.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized a retrospective cohort study design to examine HIV seroconversion and associated factors among FSWs participating in the Sauti project between October 2016 and September 2018. During this period, the Ministry of Health, Community Development, Gender, Elderly, and Children (MoHCDGEC) designated 14 regions on Tanzania's mainland to the Sauti Project to implement community-based interventions, as reported in the previous studies ( 10 , 11 ). These regions included Dodoma, Singida, Tabora, Dar es Salaam, Morogoro, Mtwara, Shinyanga, Arusha, Kilimanjaro, Manyara, Iringa, Mbeya, Njombe, and Songwe ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The trained healthcare workers and laboratory professionals used the nationally approved HIV testing algorithm involving HIV rapid diagnostic tests: SD Bioline HIV ½ (Standard Diagnostics Inc., Suwon, Korea) for screening and Uni-Gold Recombigen HIV test (Trinity Biotech, Wicklow, Ireland) for confirmation of infections. We used the Enzyme-linked immunosorbent assay (ELISA) tests, Murex HIV Ag/Ab Combination (DiaSorin S.p.A., UK Branch), and Enzygnost HIV Integral 4 ELISA (Siemens Healthcare, Germany) to resolve discordant results between the two HIV rapid tests ( 11 , 16 ).…”
Section: Methodsmentioning
confidence: 99%